Toward clinically applicable biomarkers for asthma: An EAACI position paper. Issue 10 (25th October 2019) - Diamant, Zuzana; Vijverberg, Susanne; Alving, Kjell; Bakirtas, Arzu; Bjermer, Leif; Custovic, Adnan; Dahlen, Sven‐Erik; Gaga, Mina; Gerth van Wijk, Roy; Giacco, Stefano Del; Hamelmann, Eckard; Heaney, Liam G.; et al.
Abstract: Inflammation, structural, and functional abnormalities within the airways are key features of asthma. Although these processes are well documented, their expression varies across the heterogeneous spectrum of asthma. Type 2 inflammatory responses are characterized by increased levels of eosinophils, FeNO, and type 2 cytokines in blood and/or airways. Presently, type 2 asthma is the best‐defined endotype, typically found in patients with allergic asthma, but surprisingly also in nonallergic patients with (severe) asthma. The etiology of asthma with non‐type 2 inflammation is less clear. During the past decade, targeted therapies, including biologicals and small molecules, have been increasingly integrated into treatment strategies of severe asthma. These treatments block specific inflammatory pathways or single mediators. Single or composite biomarkers help to identify patients who will benefit from these treatments. So far, only a few inflammatory biomarkers have been validated for clinical application. The European Academy of Allergy & Clinical Immunology Task Force on Biomarkers in Asthma was initiated to review different biomarker sampling methods and to investigate clinical applicability of new and existing inflammatory biomarkers (point‐of‐care) to support diagnosis, targeted treatment, and monitoring of severe asthma. Subsequently, we discuss existing and novel targeted therapies for asthma as well as applicable biomarkers. Abstract :